Efektivitas Penggunaan Aplikasi Google Classroom dalam Meningkatkan Kualitas Pembelajaran PAI Mahasiswa IAIN Curup pada Masa Pandemi Covid-19 - Okni Aisa Mutiara Sendi; Eli Susanti (Belajea: Jurnal Pendidikan Islam, 2021)
To avoid the spread of Covid-19, the learning process is carried out through online method, including IAIN Curup. Since April 2020 IAIN Curup has been implementing online learning. During online learning, the lecturers use various online applications to support the learning process so that it can run well. The purpose of this study is to discover how the effectiveness of using Google Classroom application to improve learning quality of IAIN Curup students during the Covid-19 pandemic. This research used qualitative approach, data analysis used qualitative analysis methods by using non-statistical techniques. Reserach data were collected from interviews, observation and documentation. This research shows that the effectiveness of learning by using Google Classroom is quietly effective by using strategies in the form of assignments and observations, problem-based learning models and field experiences, evaluation in the form of questions and product creation. Google classroom has several advantages such as: easy to use, saves mobile data, collects tasks precisely and saves storage memory. Meanwhile, the disadvantage is that communication is not well established